Comparison of Sr–Nd–Pb isotopes in insoluble dust between northwestern China and high-latitude regions in the Northern Hemisphere. (1st October 2019) - Du, Zhiheng; Xiao, Cunde; Dou, Tingfeng; Li, Shutong; An, Hongmin; Liu, Shiwei; Liu, Ke
Abstract: To determine the potential sources of dust at high latitudes in the Northern Hemisphere, this study measured the stable isotopic ratios of strontium (Sr), neodymium (Nd) and lead (Pb) in insoluble dust in snow samples (as well as in soil and sand samples) from sites in northwestern China and high latitudes in the Northern Hemisphere: Altay (Xinjiang, China), Ny-Ålesund (Svalbard), Barrow (Alaska) and the Arctic Ocean. The combined plots of the Sr–Nd–Pb isotopic data demonstrate that there are distinctive geographic patterns among the different sampling sites. The Sr–Nd results from the Altay (Xinjiang) and Ny-Ålesund (Svalbard) sites display overall crust-like isotopic patterns, indicating that local mineral sources represent a significant contribution. The 87 Sr/ 86 Sr and εNd (0) data from the sea ice snow samples from the Arctic Ocean and snow samples from Barrow (Alaska) suggest potential long-range dust transport to the Arctic region. Our results indicate that Russia may be a source of anthropogenic pollutants for the high Arctic region, while North America may be a source of anthropogenic pollutants for Barrow, Alaska. These findings are beneficial for protecting the environment at the global scale. Graphical abstract: Image 1 Highlights: New Sr–Nd–Pb data from Arctic and western Chinese snow samples are presented. East Asian deserts are the primary dust source for the Arctic regions. The anthropogenic pollutants in Arctic regions may be from Russia and North America.